Situational leadership and its relationship to crisis management among Jordanian universities - Bataineh, Omar Taissir; Bany Issa, Hytham Mohmmad; Al-Zoubi, Zohair Hussein (Institute of Advanced Engineering and Science, 2025)
This study investigates the extent of situational leadership practice and its correlation with crisis management among heads of academic departments in Jordanian universities, as perceived by faculty members. Employing a descriptive-correlational approach, the study sampled 405 faculty members in Jordanian universities for the spring semester of 2022/2023. To collect data situational leadership scales and crisis management scale were used. The findings revealed a high degree of situational leadership practice and crisis management effectiveness among department heads. Moreover, a statistically significant relationship between situational leadership and crisis management is observed. The study suggests selecting department heads with strong competencies and involving faculty members in crisis management courses to enhance overall effectiveness.